NeoAct: A Randomized Prospective Pilot Study on Communication Skill Training of Neonatologists - Bibl, Katharina; Wagner, Michael; Steinbauer, Philipp; Gröpel, Peter; Wimmer, Sabrina; Olischar, Monika; Berger, Angelika; Hladschik-Kermer, Birgit (Frontiers in Pediatrics, 2021)
This randomized interventional study evaluated the impact of a one-time experiential communication skills training on neonatologists’ performance in doctor-parents-communication. 17 neonatologists with different levels of professional experience from the Medical University of Vienna were randomized into one of two study groups: The intervention group (IG) as opposed to the control group (CG) participated in a one-day experiential communication training. Eight weeks after the training, participants’ communication skills were assessed during an objective structured clinical examination (OSCE). Neonatologists were assessed in a simulated conversation by how effectively they performed when conveying complex health-related information to parents of ill infants. Participants in the control group (CG) were assessed first during the OSCE and received their communication training later on. Self-assessment questionnaires before and after the workshop and OSCE were completed. The study determined that neonatologists in the IG subjectively perceived that their competence level regarding their communication skills had increased after the workshop, while this was not reflected by their performance during the OSCE assessment. A one-day experiential communication skills training significantly increased physicians’ self-evaluation concerning their communicative skills and competence. However, this perceived competence did not manifest itself in increased communication skills during the OSCE.